Using Multi-Platform Satellite Observations to Study the Atmospheric Evolution of Brown Carbon in Siberian Biomass Burning Plumes - Konovalov, Igor B.; Golovushkin, Nikolai A.; Beekmann, Matthias; Turquety, Solène (Remote sensing (Basel, Switzerland), 2022)
A bulk of evidence from in situ observations and lab experiments suggests that brown carbon (light-absorbing organic compounds in particles) can provide a significant yet highly variable contribution to the overall light absorption by aerosol particles from biomass burning (BB). Partly stemming from the complexity of the atmospheric evolution of organic aerosol (OA), the variability in brown carbon (BrC) absorption makes it difficult to partition the radiative effects of BrC and black carbon (BC) in atmospheric and climate models; as such, there are calls for satellite-based methods that could provide a statistical characterization of BrC absorption and its evolution in different regions of the world, especially in remote BB regions, such as Siberia. This study examined the feasibility of the statistical characterization of the evolution of BrC absorption and related parameters of BB aerosol in smoke plumes from intense wildfires in Siberia through the analysis of a combination of data from three satellite instruments: OMI (Ozone Monitoring Instrument), MISR (Multi-Angle Imaging SpectroRadiometer), and MODIS (Moderate Resolution Imaging Spectroradiometer). Using a Monte Carlo method, which related the satellite retrievals of the absorption and extinction aerosol optical depths to Mie theory calculations of the optical properties of BB aerosol, we found that the BrC absorption, as well as the imaginary refractive index for the OA, decreased significantly in Siberian BB smoke plumes during about 30 h of the daylight evolution, nevertheless remaining considerable until at least 70 h of the daylight evolution. Overall, the study indicated that the analysis of multi-platform satellite observations of BB plumes can provide useful insights into the atmospheric evolution of BrC absorption and the partitioning of BrC and BC contributions to the total light absorption by BB aerosol.